Evaluasi Efektivitas Pengawasan Dalam Pelaksanaan Fungsi Inspektorat (Studi Kasus Pada Inspektorat Daerah Kabupaten Garut) - Iyul Hendriyani; Ahmad Syarief (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
The problems faced by the Garut District Inspectorate have not carried out activities in accordance with the planned targets and their realization, especially in relation to time. This research is to know and explain the implementation process, constraints in implementation, the cause of implementation constraints and the effectiveness of implementing functions carried out by the Garut District Inspectorate. This type of research is qualitative research with a case study approach. The results of the study showed that the implementation of the function of garut district inspectorate was in accordance with the regulations and regulations. The effectiveness of the supervision of Garut District Inspectorate has not been effective because of the three indicators, namely the target, objectives and time has not been achieved entirely due to the amount of work while the quantity of human resources is limited so that the implementation time becomes late.